2013
DOI: 10.1007/s10592-013-0446-2
|View full text |Cite
|
Sign up to set email alerts
|

Concordant mitochondrial and microsatellite DNA structuring between Polish lowland and Carpathian Mountain wolves

Abstract: Phylogeographic studies of highly mobile large carnivores suggest that intra-specific genetic differentiation of modern species might be the consequence of the most recent Pleistocene glaciation. However, the relative influence of biogeographical processes and subsequent humaninduced population fragmentation requires a better understanding. Poland represents the western edge of relatively continuous distributions of many wide-ranging species, e.g. lynx (Lynx lynx), wolves (Canis lupus), moose (Alces alces) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 73 publications
10
80
4
Order By: Relevance
“…These methods detected two genetic clusters within Eastern Europe, one prevailing in northeastern Europe and another in the Carpathians and the Balkans, but with high level of admixture. Lack of clear, geographically clustered genetic subdivision within the Eastern European wolves contrasted with an earlier study that showed cryptic population structure in this region based on 14 microsatellite loci and mtDNA variability (Pilot et al, 2006), which was subsequently confirmed based on an independent sample set collected from a smaller area (Czarnomska et al, 2013). The discrepancy is likely due to much lower sample coverage, as 54 Eastern European wolves were analysed here versus 643 wolves in Pilot et al (2006).…”
Section: Genome-wide Diversification In European Wolves M Pilot Et Alcontrasting
confidence: 39%
“…These methods detected two genetic clusters within Eastern Europe, one prevailing in northeastern Europe and another in the Carpathians and the Balkans, but with high level of admixture. Lack of clear, geographically clustered genetic subdivision within the Eastern European wolves contrasted with an earlier study that showed cryptic population structure in this region based on 14 microsatellite loci and mtDNA variability (Pilot et al, 2006), which was subsequently confirmed based on an independent sample set collected from a smaller area (Czarnomska et al, 2013). The discrepancy is likely due to much lower sample coverage, as 54 Eastern European wolves were analysed here versus 643 wolves in Pilot et al (2006).…”
Section: Genome-wide Diversification In European Wolves M Pilot Et Alcontrasting
confidence: 39%
“…Observed heterozygosity at microsatellite loci (0.654) was comparable with populations from northeastern Europe (e.g. 0.663 for European Russia, Sastre et al 2011;0.680 for Finland, Aspi et al 2006), but higher than in the Apennine Peninsula, the Iberian Peninsula, and Poland (0.52-0.62; Fabbri et al 2007;Sastre et al 2011;Czarnomska et al 2013) (Table S6). Although comparisons of genetic diversity between different studies are not linear, given that different mtDNA sequence lengths and different microsatellite loci were used, important information can nevertheless be obtained by such comparisons, particularly if population history and present conservation status are taken into account.…”
Section: Discussionmentioning
confidence: 63%
“…Genetic diversity of the Bulgarian wolf population Diversity levels of Bulgarian wolves at mtDNA control region (Hd = 0.75, p = 0.022) were high as compared with other European wolf populations from European Russia, Poland, and Iberian Peninsula, with Hd range 0.34-0.67 and p range 0.009-0.016 (Sastre et al 2011, Czarnomska et al 2013 (Table S6). Observed heterozygosity at microsatellite loci (0.654) was comparable with populations from northeastern Europe (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The re-colonisation started from jump dispersal, which allowed wolves to establish packs far (376 ± 106.5 km) from the source population in EPL (Czarnomska et al, 2013;Nowak and Mysłajek, 2016).…”
Section: Introductionmentioning
confidence: 99%